Correlation of The Physical Properties of Nyamplung Oil-Based Biodiesel: Density, Viscosity, Calorific Value, and Flash Point - Wahyudi, Wahyudi (Journal Research of Social Science, Economics, and Management, 2025)
The increasing demand for renewable energy has intensified the development of biodiesel from various feedstocks, including non-food sources like nyamplung oil (Calophyllum inophyllum). However, the physical properties of biodiesel, such as density, viscosity, flash point, and calorific value, critically impact its performance, safety, and energy efficiency. This study aims to analyze the correlations among these key physical parameters in biodiesel blends of nyamplung oil and palm oil. Biodiesel was produced via esterification and transesterification, blended in varying ratios, and subjected to standardized testing. Regression analysis revealed a strong positive correlation between density and viscosity (R² = 0.8834) and viscosity and flash point (R² = 0.9343), while density and calorific value showed a strong negative correlation (R² = 0.9522). Flash point also negatively correlated with calorific value (R² = 0.8570). These results indicate that fatty acid composition, particularly chain length and unsaturation level, significantly affects biodiesel’s physical and energetic characteristics. Understanding these interrelations is essential for optimizing biodiesel blends to balance combustion efficiency, fuel safety, and storage stability. This research contributes valuable insights for biodiesel formulation from local resources, promoting sustainable energy solutions. Future studies should explore the impact of these physical parameters on engine emissions and durability, as well as blending effects with other indigenous feedstocks to expand applicability.